Preparation and properties of de-proteinized natural rubber latex - Huang Mao-Fang; Chen Xiao-Guang; Chen Ying; Wang Gui-An; Xu Kui; Yuan Xiao-Long (Proceedings of IRRDB Symposium 1999, Hainan, Peoples Republic of China. pp.423-428.)
The preparation, properties and the variations of properties during the natural storage and application of De-Proteinized Natural Rubber Latex (DPNRL) were studied. The results showed that the preparing conditions are affected by the enzyme dosage, and the incubating time and temperature. The physical and film forming properties of DPNRL prepared are good, whereas the mechanical stability time (MST) and heat stability time (HST) are low and are needed be raised by the addition of stabilizer.
Keywords: De-proteinization; Natural rubber latex; Properties